2019
DOI: 10.1111/jce.14171
|View full text |Cite
|
Sign up to set email alerts
|

Minimal defibrillation thresholds and the correlation with implant position in subcutaneous implantable‐defibrillator patients

Abstract: Background Since the introduction of the subcutaneous implantable‐defibrillator (S‐ICD) knowledge of factors elevating the defibrillation threshold (DFT), have increased. Optimal device positioning most likely results in a decrease in DFT. The PRAETORIAN score is a tool to systematically evaluate S‐ICD implant position and predict conversion success by estimating the DFT on a chest X‐ray. The objective of this study is to determine DFT in de novo S‐ICD patients. Methods De novo S‐ICD patients were enrolled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…S‐ICDs have emerged as a novel valid alternative to TV‐ICDs for the prevention of sudden cardiac death 1,9,10,14 . As suggested by the 2017 AHA/ACC/HRS guidelines, this technology might be particularly beneficial in patients with inadequate vascular access or with a high infective risk, due to the relevant complications associated with the extraction of infected transvenous leads 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S‐ICDs have emerged as a novel valid alternative to TV‐ICDs for the prevention of sudden cardiac death 1,9,10,14 . As suggested by the 2017 AHA/ACC/HRS guidelines, this technology might be particularly beneficial in patients with inadequate vascular access or with a high infective risk, due to the relevant complications associated with the extraction of infected transvenous leads 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In TV‐ICD recipients instead, a 5‐J safety margin was demonstrated as effective as a larger one when a true defibrillation threshold is attained by a strict testing protocol, 19,20 while testing VF termination resulted hardly meaningful in the setting of a large safety margin 5,6,8 . Indeed, there is convincing evidence that S‐ICD safety margin is larger than expected, conversion rate at ≤40 J approaching 90% in three recent studies collecting about 400 patients 13,14,21 . Owing to its probabilistic nature, DT by a single VF induction should be questioned due to limited reproducibility, while multiple VF inductions are required to establish the true defibrillation threshold 22 .…”
Section: Discussionmentioning
confidence: 99%
“… Implant position Recently, a computer model study identified three factors that alter the defibrillation threshold in S‑ICD patients: 1) fat tissue underneath the coil, 2) fat tissue underneath the generator and 3) an anterior placement of the generator on the thoracic wall [ 17 ]. When implanting physicians alter their implanting technique with these aspects in mind, step-down testing showed a lower average defibrillation threshold [ 18 ]. When implanted intermuscularly with subsequently no fat tissue underneath the generator, another study demonstrated a successful DFT at ≤40J in 94% of the patients [ 19 ].…”
Section: Comprehension Of Defibrillation Successmentioning
confidence: 99%
“…To reduce the defibrillation threshold of S‐ICDs, computer simulations suggest that the generator should be implanted closer to the chest wall and dorsally 6 . There is a PRAETORIAN score that predicts whether the defibrillation threshold will be higher based on the implantation position, 7 and if the PRAETORIAN score is low, defibrillation could be achieved at a lower energy output than in the past 8–10 …”
Section: Introductionmentioning
confidence: 99%